The impact of boot camps and traditional institutions on juvenile residents: perceptions, adjustment, and change - MacKenzie, Doris Layton; Wilson, David B.; Armstrong, Gaylene Styve; Gover, Angela R. (Journal of research in crime and delinquency, 2001)
Experiences of 2,668 juveniles in 26 boot camps were compared to 1,848 juveniles in 22 traditional facilities. There were no reported differences between juveniles' anxiety and depression in the two types of facilities during their first month of confinement. Overall, juveniles in boot camps perceived their environment to be more positive i.e., therapeutic, less hostile i.e., dangerous, and as providing less freedom conversely more structure than juveniles in traditional facilities. Relative to others in the same facility, youth who viewed their facility negatively experienced more stress i.e., anxiety, depression. Scales measuring changes over time found that youth in boot camps became less antisocial and less depressed than youth in traditional facilities. However, analyses suggest that it was not the facility type but positive perceptions of the environment that determined these changes. Furthermore, youth with histories of abuse reported higher levels of stress and exhibited less improvement overall, faring better in traditional facilities